APLIKASI ETIKA TASAWUF AL-GHAZALI DALAM MEWUJUDKAN GOOD GOVERNANCE DI INDONESIA - Agus Iswanto (Millah: Journal of Religious Studies, 2007)
This article tries to exspose that apllication of tasawuf ethics may be done to actualize Good Governance in Indonesia. The first, I give some argument why I choose tasawuf and Ghazali as a focus in this study. Tasawuf as an Islamic tradition and capacity of Ghazali are two arguments which can be used. Contextualisation of social live of Ghazali can be examined why I choose him. There are three concept from his thought about tasawuf ethic: zuhd, teleologis ethic, and ummahât al-fadhâil. These concepts can be done to practice in reforming Indonesian Good Governance.